Teachers’ Strategies in Utilizing Digital Based Instructional Materials to Enhance Students’ Learning Motivation in Akhlak Courses at an Indonesian Islamic Boarding School - Manisha Victoria; Muhammad Sabli; Andryadi Andryadi; Wiwin Narti; Ulfa Adilla (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
This study examines how Akhlak teachers design and enact strategies for using digital instructional materials to raise student learning motivation in a traditional Indonesian pesantren setting. Employing a qualitative case study design at Pondok Pesantren Darul Ulum Rimbo Bujang in Jambi Province, the research drew on participatory observation across twelve weeks of instruction, semi structured interviews with two Akhlak teachers, four eleventh grade students, and one pesantren administrator, and a documentary review of lesson plans and digital teaching artifacts. Data were analyzed through the Miles, Huberman, and Saldaña interactive model, with credibility established through source and method triangulation, prolonged engagement, and member checking. The analysis surfaces three interlocking findings. First, baseline motivation was depressed by a combination of one way lecturing, low perceived relevance, fatigue from a dense pesantren timetable, and constrained digital infrastructure. Second, teachers responded by gradually building Technological Pedagogical Content Knowledge through self directed learning and peer collaboration, then redesigning Akhlak content into short videos, animated narratives of prophetic exemplars, and case based e modules circulated through a controlled channel. Third, a flipped blended arrangement, paired with formative quizzes and reflective journals, produced observable shifts in attendance, classroom participation, and the students’ capacity to connect Islamic ethical concepts to lived dilemmas. The study argues that digital materials become motivationally effective in pesantren only when teacher competence, content design, and institutional adaptation move together